1340 Should Torch Screen Routinely Performed in Asymptomatic Symmetrical Small for Gestational Age (SGA) Babies?. (October 2012) - Gupta, A; D'Ambrosio, S; Suresh, P; Saran, S; Gupta, S
Abstract : Background and Aims: The causes of symmetrical SGA babies include infection during intrauterine period. Screening for Toxoplasmosis, Rubella, Cytomegalovirus and Herpes (TORCH) is routinely performed in these SGA babies to identify the infective cause of growth restriction. This study was carried out to study the usefulness of routine TORCH screening in symmetrical SGA babies. Methods: Newborn babies were identified from the immuno-pathology database of University hospital of North Tees for whom TORCH screening was requested from 1st January 2008 to 31st December 2011. The demographic and clinical details of all identified babies were obtained from the case notes and results of TORCH screen mapped to each baby. The reason for each request was obtained. Based on clinical details and coding each baby was grouped into symptomatic or asymptomatic group. Results: Over the 4 year study period there were 15000 babies born in this hospital. There were 153 TORCH screens requested in this period. Of these 70 were requested for symmetrical SGA babies. All asymptomatic symmetrical SGA babies had negative results of TORCH titres. Only 2 babies were positive for cytomegalovirus infection and both of these had signs of congenital infection such as thrombocytopenia and hepato-splenomegaly. Conclusions: TORCH screening should only be requested when clinical signs or symptoms of congenital infection are present. There is no justification of routinely testing asymptomatic SGA babies for TORCH titres.